Assessing the performance of primary health centres under decentralized government in Kerala, India - D VARATHARAJAN, R THANKAPPAN1 AND SABEENA JAYAPALAN (HEALTH POLICY AND PLANNING; 19(1) 2004: 41-51, 2004)
Kerala's government health-care system functions relatively well compared with other Indian States, but utilization levels are decreasing due to lack of essential facilities. The opportunity cost of seeking medical care from the government sector is high, even for the poor, with 60-70 per cent of the poor seeking care from the private sector and spending disproportionately on health care (about 40 per cent of income compared with 2.4 per cent by the rich). In 1996, the Kerala government brought primary health centres (PHCs) under the control of local governments (panchayats).